1982
DOI: 10.1073/pnas.79.5.1511
|View full text |Cite
|
Sign up to set email alerts
|

Resonance Raman detection of structural dynamics at the active site in hemoglobin.

Abstract: The iron-histidine stretching mode in deoxyhemoglobin displays a large change in frequency and width upon lowering the temperature from 300 to 10 K. The temperature dependence ofthe data indicates the presence of dynamic processes. The dynamics of this mode in frozen hemoglobins can be qualitatively and quantitatively described as a vibrational dephasing via anharmonic coupling to other vibrations of the heme-imidazole system. The effects that occur at the melting transition in the low frequency modes cannot b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
8
0

Year Published

1982
1982
2009
2009

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 22 publications
2
8
0
Order By: Relevance
“…In human deoxy-hemoglobins (normal, mutant and chemically modified) the Fe-His stretching mode shifts from -215 cm -l for the T-state species to -221 +_ 3 cm -I for the R-state species [4,5]. In this study as well as in [11] similar frequencies were observed for the low-and highaffinity forms of deoxy-Hb (carp).…”
Section: Methodssupporting
confidence: 66%
See 1 more Smart Citation
“…In human deoxy-hemoglobins (normal, mutant and chemically modified) the Fe-His stretching mode shifts from -215 cm -l for the T-state species to -221 +_ 3 cm -I for the R-state species [4,5]. In this study as well as in [11] similar frequencies were observed for the low-and highaffinity forms of deoxy-Hb (carp).…”
Section: Methodssupporting
confidence: 66%
“…By focusing on the frequency of the iron-proximal histidine (F8) (Fe-His) stretching mode it is seen [2,3] that ligand binding causes a change in the heme-proximal histidine linkage that results in an increased frequency for the Fe-His stretching mode in the photolyzed species (at 10 ns) relative to that of the corresponding deoxy species. For both the deoxy [4,5] and the photolyzed [2,3] species the R state Hb's have the higher frequency. Here, we show that this same type of structural response, of the binding site to the ligand as well as the sensitivity of this response to quaternary structure is also in evidence in carp hemoglobin.…”
Section: Introductionmentioning
confidence: 99%
“…As shown in Figure 6, for Mb, a down-shift in the ν Fe-His frequency was observed in D 2 O. The H 2 O-D 2 O isotopic shift was calculated to be 1.5 cm −1 based on the method reported previously,58 with the assumption that the ν Fe-His mode can be described by a Gaussian function 59. The same experiment was performed with iNOS P420 , but no isotopic shift was detected for the analogous 221 cm −1 mode.…”
Section: Resultsmentioning
confidence: 87%
“…6 (1982)]. 8. In several pilot studies, we had used limited exposure (100 to 200 msec) compared with Ito 2-second exposures.…”
mentioning
confidence: 99%